PENERAPAN JUST IN TIME PADA PENJUALAN PRODUK TENUN IKAT ROTE NDAO DI GERAI RANTI BERBASIS WEBSITE - Sina, Pramesthi Lady; Asmara, Jimi (Seminar Nasional & Konferensi Ilmiah Sistem Informasi, Informatika & Komunikasi, 2021)
Outlet Ranti is a business that is engaged in sales with the product being sold, namely weaving tie and accessories. The products in the Ranti outlet are taken from woven fabric manufacturers for resale, resulting in a buildup of goods due to the unsold of several products. Currently, the inventory process carried out by Ranti outlets is not efficient, resulting in excessive accumulation of goods, taking up space and damaged goods that have been stored for a long time. The purpose of the research is to apply just-in-time website-based on the sale of ikat products at Ranti outlets and how to regulate the availability of goods so that there is no accumulation of goods. With the application of just-in-time based on the website, Gera Ranti can provide convenience in managing the availability of goods so that there is no accumulation.